Effect of venlafaxine on pineal melatonin and noradrenaline in the male rat. - Franklin, M; Clement, E; Campling, G; Cowen, P (1998)
Studies in vitro indicate that the antidepressant drug, venlafaxine (VEN), inhibits the reuptake of both serotonin (5-hydroxytryptamine, 5-HT) and noradrenaline (NA) but has little activity on other neurotransmitter receptors. There are, however, few studies on the effects of VEN on monoamine neurotransmission in vivo. In the present study we examined the effect of VEN treatment on the melatonin content of the rat pineal gland because the synthesis of melatonin is regulated by the release of NA onto pinealocyte beta-adrenoceptors. Acute treatment with higher doses (15 mg/kg) of VEN significantly increased pineal melatonin and NA but this effect was attenuated by subchronic treatment. These data are consistent with in vitro data suggesting that VEN increases NA neurotransmission at higher doses and that repeated treatment can desensitize pinealocyte beta-adrenoceptors.